A lokalitás reneszánsza: Vári Anna-Joanne Caddy (eds) Public Participation in Environmental Decisions: Recent Developments in Hungary. (Budapest: Akadémiai Kiadó 1999.) - Radácsi, László; Pataki, György (Szociológiai Szemle, 2024)
-